Judicial Pardon as a Humanizing Approach to Criminal Sentencing: Reconstructing Judicial Decisions under the New Indonesian Criminal Code: Pengampunan Hukum sebagai Pendekatan Humanis dalam Penetapan Hukuman Pidana: Rekonstruksi Keputusan Peradilan di Bawah Kitab Undang-Undang Hukum Pidana Indonesia yang Baru - Rohadhatul Aisy (Universitas Negeri Semarang, 2025)
The reform of Indonesia’s criminal law through Law Number 1 of 2023 marks a major shift in the nation’s sentencing philosophy, most notably through the introduction of judicial pardon (rechterlijk pardon). This mechanism authorizes judges to declare a defendant guilty while refraining from imposing punishment when strong humanitarian grounds and proportionality considerations justify such an outcome. This article examines the normative foundations, theoretical frameworks, and implications of this concept for the reconstruction of criminal judgments in Indonesia. Using a normative juridical research method with statutory, conceptual, and comparative approaches, the study analyzes how Articles 51–54 of the new Criminal Code reorient punishment away from a purely retributive model toward a more restorative and humanistic paradigm. The findings demonstrate that judicial pardon addresses a long-standing procedural gap that previously limited judges’ ability to avoid disproportionate punishment, particularly in minor cases involving vulnerable offenders. This article also proposes a structured model for judicial pardon decisions to ensure consistent, transparent, and harmonized application with the forthcoming Criminal Procedure Code. Overall, the study argues that judicial pardon is not merely an additional judicial discretion but a key component of a broader paradigmatic shift toward a more just, contextual, and socially responsive sentencing system.